2021
DOI: 10.11113/aej.v11.18102
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Angle, Length and Brim Height of the Diffuser for the Small Diffuser Augmented Wind Turbin

Abstract: This paper presents the performance of the diffuser augmented wind turbine (DAWT) with the various diffuser shapes using the numerical investigations. DAWT is also a type of wind turbine and the diffuser shapes, the nozzle shapes and the cylindrical shapes are commonly inserted around the horizontal axis wind turbine (HAWT) to become the more efficient wind turbine. The aim of this study is to find the more efficient design of the diffuser for the horizontal axis wind turbine using the numerical investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, it was required to support the hierarchy in the model. On the other hand, it is interesting to note that the increase in velocity augmentation ratio with the increase in diffuser length was reported in previous publications [33,36,54,91,93,94].…”
Section: Interaction Effects Of Geometrical Parameters On Velocity Au...supporting
confidence: 63%
See 2 more Smart Citations
“…However, it was required to support the hierarchy in the model. On the other hand, it is interesting to note that the increase in velocity augmentation ratio with the increase in diffuser length was reported in previous publications [33,36,54,91,93,94].…”
Section: Interaction Effects Of Geometrical Parameters On Velocity Au...supporting
confidence: 63%
“…Concurrently, the augmentation of velocity for diffusers is significantly influenced by the length of the diffuser and its opening angle [31][32][33][34]. Moreover, adding a flange to the diffuser is thought to further improve velocity augmentation [11,[35][36][37]. While the cylindrical section primarily serves as a housing for the turbine, its throat length is crucial as it can influence airflow, thereby affecting velocity augmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of the optimization revealed that compact designs could achieve a 12-14% enhancement in power performance. Maw (2013) [116] conducted a sensitivity analysis of the diffuser's angle, length, and brim height using numerical simulations. The study found that a diffuser length with an aspect ratio of L/D = 1, a brim height ratio of H/D = 0.35, and a converging angle of 10 • can lead to nearly 50% higher performance compared to the baseline diffuser design from their previous research, which resulted in a 25% increase in performance.…”
Section: Mechanism Of Wind Power Harvesting: Passive Techniques 41 Gu...mentioning
confidence: 99%
“…The second power is expressed in equations 1 and 2 [21]. Tip Speed Ratio is the ratio of the tangent speed or tangent speed at the tip of the blade or blade tip with the actual fluid velocity, shown in equation 3 [22]. The power coefficient is defined as the ratio between the actual power generated by the rotor blades and the power acting on the fluid, as shown in equation 4 [23].…”
Section: Preparation Design and Analysismentioning
confidence: 99%